Benchmarking Management Practices And Manufacturing Performance Of Manufacturing Companies In Penang - LONG, LEE HEE (2005)
Benchmarking is a way of measuring an organization’s strategies and performance against best-in-class companies, both inside and outside the industry. The aim is to identify best practices that can be adopted and implemented by the organization with the purpose of improve a company’s performance. Focus has evolved from benchmarking as a means to improving company performance through the identification of best practice, to the need to identify, manage and transfer best practices.